Study on Seepage Characteristics and Production Capacity Characteristics of Complex Structural Wells in Non-Homogeneous Gas Reservoirs Based on Hydroelectric Simulation - Hengjie Liao; Quanzhi Ji; Zhehao Jiang; Bin Yuan (Energies)
With the aim of the limitations of the existing hydroelectric simulation experiment methods under non-homogeneous reservoir conditions, this paper investigates the seepage characteristics and production capacity laws of complex structural wells by designing hydroelectric simulation experiments of horizontal wells and planar multi-branch wells under non-homogeneous reservoir conditions, based on the hydroelectric similarity principle. The experiments use a CuSO4 solution and gel to simulate homogeneous and non-homogeneous reservoirs, respectively, and combine with similarity theory to construct the correspondence between the seepage field and the electric field, and to analyze the pressure distribution and the change in production. The results show the following: non-homogeneity significantly alters seepage paths, leading to a reduction in the actual control area; the superimposed effects of branching interference of planar multi-branching wells, and the non-homogeneity of the reservoir, increase the effectiveness of mobilizing the low-permeability area between the branches; the daily gas production of the horizontal wells and the planar multi-branching wells under non-homogeneous conditions are 37.6 × 104 m3/d and 70.9 × 104 m3/d, respectively; and the production gap widened with the increase in the pressure function difference as compared to the homogeneous conditions. This study provides an experimental basis for the development of non-homogeneous gas reservoirs, and it has reference value for the study of seepage mechanism and optimization of well design.